Social Impact of Digital Payment Technology Adoption in Developing Countries: A Financial Literacy Based Qualitative Study - Lina Nur Hidayati (Start-up and Financial Technology, 2025)
Objective: This research aims to assess the social impact of adopting digital payment technologies in developing countries with a focus on financial literacy, especially among vulnerable groups with low financial literacy. Research Design & Methods: This research uses a qualitative approach with a literature study, analyzing relevant previous studies. Data was drawn from recent literature on adopting digital payments in developing countries and its impact on financial inclusion, literacy, and consumer behavior. Findings: This research shows that digital payment technologies can accelerate financial inclusion, but inequality in financial literacy is a significant barrier for low-income groups to experience the benefits fully. People with low financial literacy face higher security risks and difficulties accessing digital payment services. Implications & Recommendations: The importance of more intensive and inclusive financial literacy education so that vulnerable groups can optimally utilize technology. Digital education programs should be specifically designed to improve financial understanding and skills at the grassroots. Contribution & Value Added: This research offers insights for policy makers and financial service providers on the importance of strengthening financial literacy in an effort to expand equitable adoption of digital payment technologies.